Leisure Myths and Mythmaking: Introduction to the Special Issue. (2nd November 2021) - Lashua, Brett; Baker, Simon; Glover, Troy D.
Abstract: This Special Issue centralizes powerful leisure stories that may otherwise be understood as myths—sometimes recognized, often less so—that circulate in the field, and beyond. In everyday use, a myth perpetuates a popularly held belief that is false or untrue. However, in social and cultural theory, myths are more complex, as partial truths that privilege particular versions of a shared social reality. We want to know what myths are, what they "do", and how they circulate and shape people's leisure lives. Myths can do more than obfuscate—they often animate people's lives, motivate collective action, and inspire change. In this Introduction, we map out the aims of the Special Issue to establish the conceptual terrain of leisure myths and mythmaking, and explore definitions and uses of myths, which are then brought into sharper focus in the eight papers that comprise the collection.